2022
DOI: 10.1162/edfp_a_00338
|View full text |Cite
|
Sign up to set email alerts
|

Your Pay or Someone Else's? Exploring Salary Dispersion, Position, and Principal Turnover

Abstract: This study explores ways in which salary can be structured to reduce leadership shortages by investigating how comparative wage dispersion and position alter the relationship of salary to principal turnover. Using a seventeen-year longitudinal dataset covering over sixteen thousand principals in Texas, discrete-time hazard models demonstrate that principals are highly sensitive to salary comparisons over and above basic salary. Higher comparative position is associated with significantly reduced turnover risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Past Research. Past research has used Tier 1 through Tier 3 data to examine the number of individuals obtaining principal licensure (e.g., Lankford et al, 2003), the percentage of individuals obtaining licensure who became employed as an assistant principal or principal (e.g., Bastian & Henry, 2015;Davis & Anderson, 2020), the years from licensure to employment as a principal (e.g., Davis et al, 2017;, the length of time between employment as an assistant principal to principal (Bailes & Guthery, 2020;Crawford & Fuller, 2017), distribution of principals (e.g., Clotfelter et al, 2006;Loeb et al, 2010), principal turnover (e.g., Snodgrass Rangel, 2018), and principal mobility patterns (e.g., Baker et al, 2010) In general, this body of research using state administrative data sets (mostly data from Missouri, New York, Illinois, North Carolina, Tennessee, and Texas) has concluded that more individuals obtain licensure than the number of vacancies each year, between 50% and 75% of those obtaining principal licensure become employed as a principal or in a school leadership position, the average years from licensure to employment as a principal is about 5 years (Bastian & Henry, 2015;Davis et al, 2017), an increasing number of newly licensed principals become an assistant principal prior to becoming a principal (Crawford & Fuller, 2017;Fuller et al, 2019), principal attrition and turnover are higher than teacher attrition and turnover (e.g., Bartanen et al, 2019), and salaries incentivize principals to move from one school to another (e.g., Baker et al, 2010;Pendola, 2021). To what extent these findings hold across individual labor markets and states is only speculation, given the lack of available data to conduct similar studies elsewhere.…”
Section: Principal Labor Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Past Research. Past research has used Tier 1 through Tier 3 data to examine the number of individuals obtaining principal licensure (e.g., Lankford et al, 2003), the percentage of individuals obtaining licensure who became employed as an assistant principal or principal (e.g., Bastian & Henry, 2015;Davis & Anderson, 2020), the years from licensure to employment as a principal (e.g., Davis et al, 2017;, the length of time between employment as an assistant principal to principal (Bailes & Guthery, 2020;Crawford & Fuller, 2017), distribution of principals (e.g., Clotfelter et al, 2006;Loeb et al, 2010), principal turnover (e.g., Snodgrass Rangel, 2018), and principal mobility patterns (e.g., Baker et al, 2010) In general, this body of research using state administrative data sets (mostly data from Missouri, New York, Illinois, North Carolina, Tennessee, and Texas) has concluded that more individuals obtain licensure than the number of vacancies each year, between 50% and 75% of those obtaining principal licensure become employed as a principal or in a school leadership position, the average years from licensure to employment as a principal is about 5 years (Bastian & Henry, 2015;Davis et al, 2017), an increasing number of newly licensed principals become an assistant principal prior to becoming a principal (Crawford & Fuller, 2017;Fuller et al, 2019), principal attrition and turnover are higher than teacher attrition and turnover (e.g., Bartanen et al, 2019), and salaries incentivize principals to move from one school to another (e.g., Baker et al, 2010;Pendola, 2021). To what extent these findings hold across individual labor markets and states is only speculation, given the lack of available data to conduct similar studies elsewhere.…”
Section: Principal Labor Marketmentioning
confidence: 99%
“…In general, this body of research using state administrative data sets (mostly data from Missouri, New York, Illinois, North Carolina, Tennessee, and Texas) has concluded that more individuals obtain licensure than the number of vacancies each year, between 50% and 75% of those obtaining principal licensure become employed as a principal or in a school leadership position, the average years from licensure to employment as a principal is about 5 years (Bastian & Henry, 2015; Davis et al, 2017), an increasing number of newly licensed principals become an assistant principal prior to becoming a principal (Crawford & Fuller, 2017; Fuller et al, 2019), principal attrition and turnover are higher than teacher attrition and turnover (e.g., Bartanen et al, 2019), and salaries incentivize principals to move from one school to another (e.g., Baker et al, 2010; Pendola, 2021). To what extent these findings hold across individual labor markets and states is only speculation, given the lack of available data to conduct similar studies elsewhere.…”
Section: Informing Policy and Practice With Principal Pipeline Datamentioning
confidence: 99%
“…These studies generally fall into two camps: those that recognize the subjective and affective dimensions of workplace dissatisfaction (e.g., stress, low agency) and those that measure the conditions associated with turnover (e.g., low salary, student population) (Farley-Ripple et al, 2012; Rangel, 2018). Below, we explore the affective correlates of principal turnover, given that conditions, such as low salary, are experienced as dissatisfaction (Pendola, 2021), and are generally fixed in the workplace environment (e.g., schools cannot control student demographics). We organize these into intrapersonal and interpersonal sources of dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%